2008
DOI: 10.1002/cncr.23714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the supportive care costs of severe radiochemotherapy‐induced mucositis and pharyngitis

Abstract: BACKGROUND. Few studies have examined the costs of supportive care for radiochemotherapy-induced mucosits/pharyngitis among patients with head and neck cancer (HNC) or lung cancers despite the documented negative clinical impact of these complications. METHODS.The authors identified a retrospective cohort of patients with HNC or nonsmall lung cancer (NSCLC) who had received radiochemotherapy at 1 of 3 Chicago hospitals (a Veterans Administration hospital, a county hospital, or a tertiary care hospital). Charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(61 citation statements)
references
References 9 publications
0
60
0
1
Order By: Relevance
“…A recent report in which mouth and throat soreness data were collected in HNC patients revealed 80% incidence of severe OM [12]. A recent retrospective chart review found a 70% incidence of severe OM for HNC patients receiving radiochemotherapy [13]. One probable explanation of the high incidence is the effect of direct oral mucosal injury from irradiation per se.…”
Section: Discussionmentioning
confidence: 97%
“…A recent report in which mouth and throat soreness data were collected in HNC patients revealed 80% incidence of severe OM [12]. A recent retrospective chart review found a 70% incidence of severe OM for HNC patients receiving radiochemotherapy [13]. One probable explanation of the high incidence is the effect of direct oral mucosal injury from irradiation per se.…”
Section: Discussionmentioning
confidence: 97%
“…Incidence of OM was investigated in patients with hematopoietic stem cell transplantation (HSCT) in 14 studies (32.6%) [3,5,14,17,19,28,31,36,37,39,44,56,62,67], in head and neck cancer (HNC) patients in 13 studies (30.2%) [18,21,29,40,50,51,55,59,60,61,63,70,73], in patients with chemotherapy in 13 studies (30.2%) [15,16,22,23,24,25,30,34,38,46,48,58,71], with mixed tumor types and treatment in 1 study (2.3%) [13] and with palliative care in 2 studies (4.7%) [32,57]. Cost related to OM in patients undergoing HSCT was the focus in 4 studies [7,14,17,54], in HNC patients in 2 studies [43,47], in patients with chemotherapy in 6 studies [9,10,11,12,42,49,68], and in patients with mixed tumor types and treatment in 2 studies [20,45]. Resource use associated with OM was reported in 3 studies concerning patients with HSCT [3,7,17], 2 studies with HNC [4,43] and 1 study with chemotherapy [42] and 1 study with mixed tumor types and treatment [45].…”
Section: Resultsmentioning
confidence: 99%
“…Resource use was reported in 7 studies [3,4,7,17,42,43,45,] 2 of which did not include cost data [3,45]. Resource use comprised length of hospital stay (LOS), emergency department visits, hospital admission due to OM, number of clinic visits, nutritional visits, total parenteral nutrition (TPN), feeding tube, gastrostomy tube, use of opioids, and use of oral or intravenous antibiotics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations